Clinical Characteristics of Measles in Previously Vaccinated and Unvaccinated Patients in California. (7th June 2018) - Cherry, James D; Zahn, Matt
Abstract: Background: Measles vaccine failure was first described in 1972. Over the next 20 years, vaccine failure was extensively studied, but during the last 25 years few investigations have been performed. We describe the clinical characteristics of measles in previously vaccinated and unvaccinated patients in California. Methods: All confirmed measles cases reported to the California Department of Public Health from 1 January 2000 through 31 December 2015 were reviewed. Clinical characteristics (rates of hospitalization, cough, coryza, conjunctivitis, and fever) were compared between the previously unvaccinated, those who had had 1 dose of vaccine, and those who had had ≥2 doses of measles vaccine. Results: There were 232 confirmed measles cases in whom vaccination status was verified; 80% were unvaccinated, 9% had had 1 dose of measles vaccine, and 11% had had ≥2 doses of measles vaccine. Subjects who had had ≥2 doses of measles vaccine had lower rates of hospitalization, cough, coryza, conjunctivitis, and fever than subjects who had 1 dose of measles vaccine or who were unimmunized. Conclusions: Vaccine failure measles cases were less ill than cases that occurred in unvaccinated patients. Nevertheless, these cases still required the same amount of public health effort in tracing contacts as in cases who were unvaccinated. Abstract : This is the largest study of the clinical characteristics of measles in previously vaccinated and unvaccinated patients in the 21st century.